2011
DOI: 10.1103/physrevlett.107.163603
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Orientation and Alignment by Intense Single-Cycle THz Pulses

Abstract: Intense single-cycle THz pulses resonantly interacting with molecular rotations are shown to induce field-free orientation and alignment under ambient conditions. We calculate and measure the degree of both orientation and alignment induced by the THz field in an OCS gas sample, and correlate between the two observables. The data presents the first observation of THz-induced molecular alignment in the gas phase.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
255
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(261 citation statements)
references
References 49 publications
3
255
0
3
Order By: Relevance
“…A complete analytical derivation of this result is given in this paper. Note that this dependency has been already mentioned in [54]. The relation between the FID and the degree of orientation allows us to quantitatively compare the experimental observations with the numerical simulations.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A complete analytical derivation of this result is given in this paper. Note that this dependency has been already mentioned in [54]. The relation between the FID and the degree of orientation allows us to quantitatively compare the experimental observations with the numerical simulations.…”
Section: Introductionmentioning
confidence: 89%
“…Note that a larger degree of orientation can be achieved with the two-color mechanisms through ionization depletion [53]. In this second regime, molecular orientation has been recently addressed experimentally for linear molecules using only a THz field [54] or its combination with a laser field [55], and in [56,57] for an excitation process with two-color laser fields.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter mechanism, so-called sequential double ionization (SDI), two electrons are released independently step by step, therefore the SDI yield can be simulated by using ionization theory based on SAE. Nevertheless, recent experiments [7][8][9] have doubted the validity of independent-electron approximation in the SDI regime. Specifically, Fleischer et al [9] reported an angular correlation between the first and second ionization steps.…”
mentioning
confidence: 99%
“…Nevertheless, recent experiments [7][8][9] have doubted the validity of independent-electron approximation in the SDI regime. Specifically, Fleischer et al [9] reported an angular correlation between the first and second ionization steps. In Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation